Research on University Educational Administration Management Based on Blockchain Technology - Guojun (International Journal of Management and Education in Human Development, 2022)
Educational administration management is the core of university management. With the progress in the field of education, the number of students in each university is also increasing. The traditional educational administration management system has been unable to meet the current educational administration needs. In this case, a new decision support system for university educational administration management based on blockchain technology is designed to solve the problems faced by the existing decision-making system. SPI interface and decision synchronizer are designed in the hardware part; In the software part, the process of educational administration decision-making in colleges and universities is analyzed first. Secondly, the data warehouse is designed using blockchain technology. Finally, the functional structure of educational administration decision support in colleges and universities is designed to realize educational administration decision support. Experimental results show that the designed decision support system has good performance, can effectively support educational administration decisions, and has certain application value.